Pendampingan Pembelajaran Al-Qur’an Berbasis Komunitas di Desa Morosari, Kecamatan Sukorejo - Fathoni, Tamrin (Edujavare Publishing, 2024)
This community service program aimed to strengthen Qur’anic learning through a community-based mentoring approach in Morosari Village, Sukorejo District. The program was designed to address challenges in non-formal Qur’anic education, particularly limited pedagogical capacity of local instructors, unstructured learning methods, and varying levels of learners’ Qur’anic reading abilities. An Asset-Based Community Development (ABCD) approach was employed to optimize existing community assets, including local Qur’anic teachers, religious institutions, and strong social support for Islamic education. The program was implemented through several stages: community asset mapping, collective goal formulation, participatory program design, mentoring-based implementation, and reflective evaluation. Mentoring activities focused on improving Qur’anic reading skills using structured methods such as talaqqi, tahsin, and learner grouping based on reading proficiency. Local instructors were actively involved as key actors, while the service team functioned as facilitators and mentors. The results indicate a significant improvement in learners’ Qur’anic reading fluency and accuracy, particularly in pronunciation and basic tajwīd application. In addition, local instructors demonstrated increased pedagogical awareness and improved teaching practices. Community participation also increased, reinforcing collective responsibility for Qur’anic education. Overall, the community-based mentoring model supported by the ABCD approach proved effective in enhancing the quality and sustainability of Qur’anic learning. This program offers a replicable model for strengthening community-driven Islamic education in similar rural contexts.